2015
DOI: 10.2116/analsci.31.823
|View full text |Cite
|
Sign up to set email alerts
|

Multi-residue Method for Determination of Selected Neonicotinoid Insecticides in Traditional Chinese Medicine Using Modified Dispersive Solid-phase Extraction Combined with Ultra-performance Liquid Chromatography Tandem Mass Spectrometry

Abstract: A reliable and cost-effective method for the determination of multiple neonicotinoids was developed using a modified QuEChERS-based extraction procedure in complex matrices, namely Hedyotis diffusa (a representative of the Traditional Chinese herb which contains lots of pigment, saponin and terpene) and Semifluid extract of deer foetus (a representative of the Chinese traditional patent medicine that was produced with several different herbs, and especially containing lots of protein, except for other interfer… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4

Citation Types

0
4
0

Year Published

2016
2016
2024
2024

Publication Types

Select...
8
1

Relationship

0
9

Authors

Journals

citations
Cited by 15 publications
(4 citation statements)
references
References 26 publications
0
4
0
Order By: Relevance
“…Many studies have reported methods for the detection of trace pesticides, which some pesticides have endocrine activity (EDCs) [21] in Chinese herbal medicines: liquid chromatography (LC) and gas chromatography (GC) [22,23], gas chromatography-mass spectrometry (GC-MS) [24] and liquid chromatography-mass spectrometry (tandem) mass spectrometry (HPLC-MS or HPLC-MS/MS) [25]. The methods for detecting mycotoxins such as aflatoxins in traditional Chinese medicine have enzyme-linked immunosorbent assay (ELISA) [26], HPLC [27] and LC-MS/MS [28].…”
Section: Introductionmentioning
confidence: 99%
“…Many studies have reported methods for the detection of trace pesticides, which some pesticides have endocrine activity (EDCs) [21] in Chinese herbal medicines: liquid chromatography (LC) and gas chromatography (GC) [22,23], gas chromatography-mass spectrometry (GC-MS) [24] and liquid chromatography-mass spectrometry (tandem) mass spectrometry (HPLC-MS or HPLC-MS/MS) [25]. The methods for detecting mycotoxins such as aflatoxins in traditional Chinese medicine have enzyme-linked immunosorbent assay (ELISA) [26], HPLC [27] and LC-MS/MS [28].…”
Section: Introductionmentioning
confidence: 99%
“…The quality of MFH plants can be influenced by multiple factors, including soil conditions, ecological activity, and pesticide use (Huang et al, 2018;Qin et al, 2015;Ren et al, 2017). Due to the lack of a proper pesticide registration system for some MFH plants with small planting areas and/or low pesticide consumption, the number of MFH plants registered for pesticide use is currently insufficient in China.…”
Section: Introductionmentioning
confidence: 99%
“…Other instruments include gas chromatography-tandem mass spectrometry (GC-MS/MS) (29) and liquid chromatography-tandem mass spectrometry (LC-MS/MS) (30). Unfortunately, the poor sensitivity of these instruments is their major setbacks.…”
Section: Introductionmentioning
confidence: 99%